Lower extremity injury rates on artificial turf versus natural grass playing surfaces: A systematic review - Gould, H. P.; Lostetter, S. J.; Samuelson, E. R.; Guyton, G. P. (The American Journal of Sports Medicine, 2023)
Background: No study has provided a comprehensive systematic review of sports injuries on artificial turf versus natural grass.